Confocal Microscopy Study of Undisturbed and Chlorhexidine-treated Dental Biofilm - Zaura-Arite, E.; van Marle, J.; ten Cate, J.M. (Journal of dental research, 2001)
Culturing of dispersed plaque samples and vitality staining of plaque smears are the most commonly used methods for evaluating the effects of antimicrobials on dental plaque. The visualization of the antimicrobial action on oral biofilm present on the substrate surface (in situ) would add valuable information to the existing knowledge about the treatment effects. This study aimed at combining the advantage of confocal laser scanning microscopy (CLSM) to visualize plaque non-destructively with a vitality staining technique to assess the immediate bactericidal effect of chlorhexidine (CHX) on biofilm. Three 200-μmwide grooves were cut into bovine dentin discs for plaque accumulation. The discs were worn by six subjects for 6, 24, and 48 hrs, then broken into halves, one of which received a one-minute extra-oral 0.2% CHX treatment, while the other served as control. Both halves were stained for vital fluorescence measurements and visualized by CLSM. Plaque vitality (in %) was quantified by image analysis in three plaque layers-outer, middle, and inner. The CHX effect was significant in six-hour samples (p < 0.001) and only in the outer layer of the 48-hour plaque (p < 0.001), demonstrating a resistant nature of dental biofilm to a single CHX treatment. With the present approach, we have shown that it is possible to visualize and quantitate the antimicrobial treatment effect on biofilm still present on the substrate on which it was grown.